Why Do Pupils Opt out of Foreign Language Courses? A Pilot Study - Aplin, Richard (Educational studies, 1991)
Analyzes answers to a questionnaire given to British secondary school children who had opted out of foreign language study. Identifies reasons why the students chose not to continue language study. Concludes that enjoyment of the subject and opportunities for contact with the country of the target language are factors motivating students to continue language study. (DK)